THE EFFECT OF FINANCIAL PERFORMANCE AND DIVIDEND POLICY ON CUMULATIVE ABNORMAL RETURN - Rahayu, Yayuk Sri; Wardana, Guntur Kusuma (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2021)
The purpose of this study was to determine the effect of financial performance and dividend policy on Cumulative Abnormal Return for company shares in Jakarta Islamic Index. The population was all company stocks listed on The Jakarta Islamic Index from 2009 to 2018. The samples were selected by purposive sampling with the criteria the companies were consistently included in JII (not delisted and relisted) during the 2009-2018 period and those that met the criteria were five companies. Financial performance was proxies by Earning per Share, Price Earnings Ratio, Current Ratio, and Return on Equity. Meanwhile, dividend policy was proxies by the Dividend Payout Ratio. This research type was quantitative by using the panel data regression method. The results showed that Earning per Share effect on Cumulative Abnormal Return, while the Price Earnings Ratio, Current Ratio, Return On Equity and Dividend Payout Ratio variables had no effect on Cumulative Abnormal Return. The implications of this research for other parties consists of scientific development, especially in the field of financial management, and can be an input for investors in investing in shares on the Indonesia Stock Exchange (IDX) so that it can have a positive impact in the form of dividends or capital gains to investors. And can be used as a reference for further researchers by adding other variables that are not included in this study.